Effect of the addition of bio-polymer lignin on the Transverse and Impact strength of the autopolymerizing acrylic resin. - Ismail, Intisar J.; Hamad, Thikra I.; Hussein, Basima M.A. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Acrylic resin dentures are susceptible to fracture; it is unresolved problem in prosthodontics. The repair procedure should be simple, strong, and accurate. This study evaluated the transverse and impact strength of autopolymerizing acrylic resin, the repair material was modified with kraft lignin as a new enforcement material and compared with the commercially available self cured acrylic resin. Materials and Methods: The addition of kraft lignin to the acrylic resin were done in percentages of 0.25%, 0.5%, 0.75%, 1.0%, 1.25%, and 1.5% (wt%). Seventy specimens were made according to the ADA specification No 12 for transverse strength using three point bending test and Impact strength test was conducted following the procedure given by the ISO 179 with Charpy Type Impact testing instrument. Results: Mean transverse strength of experimental specimens where increased only in 0.25wt% addition of lignin (61.3400 Mpa) then results tend to decrease, and no statistical differences found between the control and any one of the modified groups. The impact strength increased more than the control in the groups 0.25, 0.50, 0.75,and 1.0wt%,13.9700, 15.5900, 35.2100, 33.6900 Kj/m2 respectively, then has been decreased at 1.50wt% until reach value of the control (9.2525 Kj/m2).Highly significant difference was found at 0.5, 0.75 and 1.0wt% (p<0.05). Conclusions: The autopolymerizing acrylic resin exhibited significantly higher impact strength as a result of addition the biopolymer lignin. The transverse strength of the modified specimens was decreased after increasing the weight percent addition of lignin.